A Doxological Necessity: The Use of Biblical, Philosophical, and Empirical Knowledge to Construct a Comprehensive Christian Psychological and Therapeutic Science. Issue 3 (September 2021) - Johnson, Eric L.
According to Stark, the motive of God's glory provided the ideological basis for the Scientific Revolution. Smith argues that by the time that revolution began to spread to the human sciences in the late 1800's and early 1900's, another revolution was emerging, with which the human sciences have become thoroughly confounded, the Secular Revolution . Following MacIntyre, Johnson suggests that this confounding has created a crisis for the Christian intellectual and soul-care traditions, but one that was largely self-inflicted. One of the consequences of this crisis has been a serious wound/division in the Christian body regarding the relation between the Bible, and its theocentric worldview and way of life, and the current form of psychology and the therapeutic sciences (psychiatry, psychotherapy, and counseling). In this article, reasons are given for imagining one way the glory of God could again become a supreme motive among Christians in Western science, specifically psychology and the therapeutic sciences, that would help to overcome the current biblical knowledge/empirical knowledge dichotomy that afflicts the Christian community in these fields and could unify and empower it to develop Christian alternatives to their mainstream versions.